THE POPULATION’S HAPINESS AND SAFETY AS PREDICTORS OF THE COUNTRY’S ECONOMIC DEVELOPMENT - Tonikyan , M. G.; Stepanyan , L. S. (Modern Psychology, 2018)
Investigation tells about the connection of reputation of the country as a combination of happiness, safety and corruption, influencing the economic development of the state. The paper researched how country’s reputation influences such economic indicators of country as foreign direct investments, GDP, revenues from tourism industry, etc. To give a score to reputation of countries we use data from Reputational Institute and other organizations that make safety, corruption and happiness ratings for worldwide countries. It was revealed, that the steps, implemented in Armenia by the government till 2018 didn’t help the country on its way of attracting foreign investments. On the other hand, we may say, that Armenia is a very safe country, which is able to bring more tourists here.